How COP27 can deliver climate justice for rural women - Haan, Nicoline C. de (Thomson Reuters Foundation, 2022)
Households in Bangladesh, where women have equal participation in decision-making, are more likely to grow a greater range of crops, a key strategy for minimising the risk that climate change poses to food security and nutrition. Women are also more likely to raise locally adapted livestock breeds that are inherently more resilient to climate stress. To drive such changes in other places – and deliver climate justice for millions of rural women – the $100 billion a year richer nations have promised to deliver in climate finance must be directed toward the worst impacted women, and men, in the most affected regions of the world. Campaigners and governments in low-income countries will have great expectations for this year’s COP27 climate talks that the $100 billion promised in 2009 will finally materialise. The UN conference, hosted by Egypt, will also be an opportunity to build on the recognition at COP26 that women and girls both face a disproportionate burden from climate change, and represent unfulfilled potential in adapting to its consequences.